Transmission of Islamic Values in Public School: A Study at State Senior High School 5 Yogyakarta - Suyatno Suyatno; Fitri Nur Hayati; Wantini Wantini (Analisa: Journal of Social Science and Religion, 2020)
The process of transmitting Islamic values to the younger generation remains an appealing study as Indonesia is a country with the largest Muslim population in the world. Unfortunately, previous studies on this topic focused more on the process of transmitting these values through formal and informal religious based educational institutions. This research took a unique position to study the Islamic values transmission within non-religious based public school. This qualitative research employed the case study approach to examine the process of instilling Islamic values in public schools. Data were collected through in-depth interviews, observation, and study of relevant documentation. The collected data were analyzed using the inductive interactive techniques of the Miles and Huberman models. This study showed that 1) the values of iman-taqwa (faith-piety) and akhlaq mulia (good morals) were an important embodiment of affection-based educational programs in schools. 2) These values were instilled by the school through a habituation process, supported by the function of the principal and teachers as role models and the important role of Rohis (Islamic organization). The inculcation of Islamic values was not only carried out by religious education teachers, but also transmitted by secular subject teachers as well as extracurricular activities. The findings of this study confirmed that public schools in Indonesia were now transformed as important instruments for the transmission of Islamic values to young Muslims. This research suggests important recommendations on the need to develop the capacity of teachers in schools to make them agents of moderation of Islamic values.